Actinic keratosis and imiquimod: a review of novel carriers and patents. (1st February 2019) - Sharma, Mandeep; Sharma, Gajanand; Singh, Bhupinder; Katare, O.P.
ABSTRACT: Introduction : Actinic keratosis is one of the most common disorder characterized by erythematic and generally attached scaly lesions which are present either alone or in clusters. World Health Organization defines actinic keratosis as a common intraepidermal neoplasm of sun-damaged skin, characterized by variable atypia of keratinocytes. Area covered : At the beginning of the 20th century, a new immunomodulator molecule, imiquimod, appears in the market for the treatment of actinic keratosis but suffers from the pitfalls of the conventional approach of dosage form preparation including high dose, poor stability and more side effects. The present article attempts to compile the scatter information related to actinic keratosis and imiquimod at one place. The special emphasis will be made on the information available in various research articles and patents with respect to the efforts made for overcoming shortcomings associated with imiquimod by novel drug delivery or other approaches. Expert opinion : The conventional drug delivery systems are unsuccessful to improve the actinic keratosis. The patient acceptance and compliance with these treatments are generally poor due to associated side effects, poor cosmetic outcomes and high costs. Therefore, several available and reported novel therapeutic approaches are being developed in order to provide better action.